Driving factors of ecosystem services and their spatiotemporal change assessment based on land use types in the Loess Plateau - Wang, Xiaozhen; Wu, Jianzhao; Liu, Yulin; Hai, Xuying; Shanguan, Zhouping; Deng, Lei (Journal of environmental management, 2022)
A clear understanding of the driving factors for different ecosystem services (ESs) is quite essential for sustainable ecosystem management. It is important to strengthen research in ESs and social sustainable development to identify the main driving factors of different ESs. This study assessed carbon sequestration (CS), water yield (WY) and soil conservation (SC) from 2000 to 2018 in the Loess Plateau using CASA (The Carnegie-AmesStanford Approach), InVEST (Integrated Valuation of Ecosystem Services and Trade-offs) and RUSLE (Revised Universal Soil Loss Equation) models. The spatial heterogeneity, trade-offs and synergies and driving factors were explored in the whole Loess Plateau. The results showed that the WY, CS and SC had increased from 2000 to 2018. The spatial relationships between WY and SC, SC and CS, and WY and CS were mainly synergistic. Annual mean precipitation (MAP) was the dominant driving factor of WY, while normalized difference vegetation index (NDVI) and slope (SL) had the strongest explanatory power for CS and SC. The LU was the most critical factor affecting the ESs in the different climatic zones. These results could act as a reference for decision-makers on how to control various influencing factors of ESs to improve the local ecology under local conditions. •Natural and anthropogenic driving factors of key ecosystem services were comprehensive studied based on different scale.•Main driving factors of key ecosystem services in the Loess Plateau were clarified.•Land use type has the most important effects on ecosystem services on the Loess Plateau.